Interaction of Biomolecules with Silver Nanoparticles Prepared via Intramolecular Redox Reaction of Ag(I) Complexes as Their Precursors - Iveta S. Turomsha; Natalia V. Loginova; Maxim Y. Gvozdev; Tatiana V. Koval’chuk-Rabchinskaya; Nikolai P. Osipovich (Chemistry Proceedings)
Nanoparticles are known to have a high specific surface area, which accounts for an increased probability of their interaction with bacterial cells. Therefore, the application of silver(I) nanoparticles (AgNPs) and their nanocomposites as antimicrobial agents against drug-resistant bacterial strains appears to be prospective. A critical point for the advancement of AgNPs into clinical practice is a fundamental understanding of their behavior in biological systems, including protein binding and interaction with blood components, which reflects their toxicity. The latter is primarily determined by the physicochemical properties of AgNPs, namely their size, shape, surface chemistry, etc. Therefore, nanotoxicity may be substantially reduced through the manipulation of certain physicochemical characteristics of AgNPs, increasing their biocompatibility and hence paving the way for possible biomedical applications. In this study we have focused on estimating the binding affinity of the synthesized Ag(I) complexes of 2-(4,6-di-tert-butyl-2,3-dihydroxyphenylsulfanyl)-acetic acid and 4,6-di-tert-butyl-2,3-dihydroxybenzaldehyde isonicotinoyl hydrazone, as well as AgNPs derived thereof to bovine serum albumin (BSA) and hemoglobin by the fluorimetric method. Furthermore, cellular toxicity of the AgNPs towards human erythrocytes was measured in a hemolysis assay. Organosols formed by the Ag(I) complexes upon their reduction to AgNPs in acetonitrile and DMSO were characterized by the transmission electron microscopy (TEM) method and atomic force microscopy (AFM).